Macroeconomic Factors and The Correlation of Stock and Bond Returns: Empirical Evidence from Kenya - Namango, Isaac Musungu (Advances in Social Sciences Research Journal, 2018)
This paper investigated how macroeconomic factors affect the correlation between stock and bond returns in Kenya over the past decade (July2006-Dec2015) using the Arbitrage Pricing Theory (APT) and Capital Asset Pricing Model (CAPM) framework for a time series of data. The study aimed to validate that the correlation of stock and bond returns could be explained by their common exposure to macroeconomic factors. The link between the stock-bond correlation and macroeconomic factors was examined using OLS regression model. With the empirical tests aimed at answering the following questions: How does inflation affect the correlation between stock and bond returns in Kenya? How do the interest rates affect the correlation between stock and bond returns in Kenya? How does money supply affect the correlation between stock and bond returns in Kenya? And how does the business cycle affect the correlation between stock and bonds? Secondary data obtained from the Kenya Central Bank, the Nairobi securities exchange and the Kenya bureau of statistics from July 2006 – December 2015 was analyzed. The empirical results confirmed that inflation rate, interest rate and business cycle do have a significant and positive influence on the stock-bond correlation. Money supply was found to have a negative influence on stock bond correlation in this study. The Ordinary Least Square Regression Model confirmed long run relationship between stock-bond correlation and the macroeconomic variables under review. The model was found to be robust because it passed all the diagnostic tests.